When Asia was the world - Gordon, Stewart, 1945- ([Cambridge, Mass.] : Da Capo Press, 2009)
While European intellectual, cultural, and commercial life stagnated during the early medieval period, Asia flourished as the wellspring of science, philosophy, and religion. Linked together by a web of religio us, commercial, and intellectual connections, the different regions of Asia's vast civilization, from Arabia to China, hummed with commerce, i nternational diplomacy, and the brisk exchange of ideas. Stewart Gordon has fashioned a look at Asia from A.D. 700 to 1500, a time when Asia w as the world, by describing the personal journeys of Asia's many travel ers--the merchants who traded spices along the Silk Road, the apothecar ies who exchanged medicine and knowledge from China to the Middle East, and the philosophers and holy men who crossed continents to explore an d exchange ideas, books, science, and culture.--From publisher descript ion.
Monasteries and monarchs : Xuanzang, 618-632 CE -- Caliph and carava n : Ibn Fadlan, 921-922 CE -- Philosopher and physician : Ibn Sina, 102 0-1036 CE -- Ingots and artifacts : the Intan shipwreck, circa 1000 CE -- Pepper and partnerships : Abraham bin Yiju, 1120-1160 CE -- Nobles a nd notables : Ibn Battuta, 1325-1356 CE -- Treasure and treaty : Ma Hua n, 1413-1431 CE -- Blood and salt : Babur, 1494-1526 CE -- Medicines an d misunderstandings : Tomâe Pires, 1511-1521 CE. -- The Asian world : 5 00-1500 CE.
Includes bibliographical references (p. 193-221) and index.
Keywords: Travelers -- Asia -- History; Asia -- Description and travel; Asia -- Civilization